Soil niche of rain forest plant lineages: Implications for dominance on a global scale - Şerban Procheş; Rahayu S. Sukri; Salwana M. Jaafar; Erwin J.J. Sieben; Nurul Hazlina Zaini; Norain Abas; Siti Nurqayah Suhaini; Nurul Maz Juhairah Manjul; Muhammad Abdul Hakeem Julaihi; David J. Marshall; J.W. Ferry Slik; Desika Moodley (Journal of Biogeography, 2019)
Aim Why some lineages are species‐rich and widespread, while others are species‐poor and localized, is a fundamental question in evolutionary biology and ecology. Diversification and range expansion relate to lineage‐specific niche characters, but this link has seldom been quantified across multiple lineages and environments. This study explored the link between local dominance and soil niche in rain forest plants, and tested the hypothesis that local soil niche patterns can be used to predict the global diversity and occupancy of equal‐aged plant lineages. Location The study was carried out in Brunei Darussalam (Borneo) and projected worldwide. Methods Our approach involved the subdivision of vascular plants into the lineages found 120 Mya, a time preceding the explosive radiation of the eudicots. We quantified the representation of the 120 Mya lineages in different forest types associated with dramatically different soils, but sharing the same climatic conditions. The forest types included primary and secondary lowland rain forest, flooded and nutrient‐impoverished inland forests, and mangroves. Niche breadth and position, estimated from the soil types that a lineage occupied, were used to predict global diversity and occupancy patterns, after accounting for relatedness to the dominant eudicots. Results Despite marked differences in soil characteristics among the forest types, three eudicot lineages (Malvidae, Fabidae, Asteridae) were consistently dominant over the other 28 lineages present. A broad, intermediate soil niche, relatedness to eudicots, and the interaction between these factors were found to be strong predictors of global diversity and occupancy. Main conclusions We show that vegetation plot data from one of the world's most diverse regions (in terms of plant species richness and ancient lineage representation) can be used to successfully predict lineage diversity and occupancy on a global scale. However, because lineage dominance likely depends on the interaction between soil niche and above‐ground factors, including above‐ground niche features should improve the accuracy of predicting global distribution and diversity—particularly when explaining eudicot dominance.